Strategi Pasangan Karir Dalam Mengoptimalkan Pola Asuh Sebagai Orang Tua Untuk Memperkuat Ketahanan Keluarga - Nurichsan (CV. ITTC INDONESIA, 2025)
Family resilience is the family's ability to ward off or protect itself from various problems or threats to life both from within the family itself and from outside the family (such as the environment, community, society, and the state), the ability of individuals to utilize their potential to face life's challenges, able to survive and adapt to various conditions. Indonesia is a developing country where the workforce consists not only of men, but also actively involves women. The Central Bureau of Statistics (BPS) obtained data on the percentage of women who have competent jobs reaching 56.70% in 2025. This figure has increased by 2.33% since last year's figure of 55.41%. This shows that there are 82.13% of families in which there are career couples. This fact shows that the phenomenon of “career couples” continues to increase from year to year. This research uses a qualitative method with a library research approach. The results of this study conclude that there are several steps that career couples can take as parents in optimizing parenting to strengthen family resilience.